Pengaruh Inovasi Digital dan Struktur Modal dengan Literasi Keuangan Sebagai Variabel Moderasi - Wima D Pragusta; Ira Hapsari; Hadi Pramono; Edi Joko Setyadi (Politeknik Ganesha Medan, 2026)
This study was conducted to analyze the influence of digital innovation and capital structure on profitability, with financial literacy as a moderating variable in MSMEs in Banyumas Regency. The method applied in this study was quantitative, with 203 MSME respondents obtained through purposive sampling. Data collection was carried out through a structured questionnaire, while data analysis used Partial Least Squares (Smart PLS) to test the interaction between variables and their moderating effects. The findings of this study indicate that digital innovation and capital structure have a positive impact on profitability, and financial literacy plays a role in strengthening the relationship between digital innovation and capital structure on profitability. This study confirms that good financial literacy skills can encourage more effective implementation of digital innovation and maximize the use of capital to improve business financial results. This study also contributes to the development of the Resource-Based View (RBV) and Dynamic Capabilities (DC), namely digital innovation is seen as a strategic capability, capital structure as a financial resource, and financial literacy as a dynamic capability that strengthens the effectiveness of decision-making.